Creativity And Innovation In Developing Human Resource Management In Islamic Schools - Suryadi, Lalu (SAINTIS Publishing, 2025)
The objectives of this study are, among others: 1) to analyze strategies and steps of creativity and innovation in developing human resource management in Islamic schools; 2) to analyze the forms of creativity and innovation in developing human resource management in Islamic schools. This research uses a qualitative approach with a library research method. The data sources refer to primary sources from the research title, while secondary sources come from journals or previous studies. Data collection techniques use library research, and data analysis techniques use content analysis, consisting of stages of data analysis and data interpretation. The results of the study show, among others: 1) The strategies and steps include: a) teacher and staff competency development, b) utilization of technology, c) innovative curriculum and learning methods, d) collaboration and partnerships, e) school culture, f) evaluation and feedback, and g) mentoring. 2) The forms of creativity and innovation in developing human resource management in Islamic schools include: a) development of Islamic training programs, b) application of technology in HR management, c) development of reward and incentive programs, d) fostering an inclusive work culture, and e) development of employee welfare programs. The implication of this research is that Islamic educational institutions should continuously develop human resources through various forms of creativity and innovation. This study also serves as a reference or previous research for future studies.